The Specific NLRP3 Antagonist IFM-514 Decreases Fibrosis and Inflammation in Experimental Murine Non-Alcoholic Steatohepatitis - Torres, Sandra; Brol, Maximilian J; Magdaleno, Fernando; Schierwagen, Robert; Uschner, Frank E.; Klein, Sabine; Ortiz, Cristina; Tyc, Olaf; Bachtler, Nadine; Stunden, James; Bertheloot, Damien; Kitanovic, Ana; et al. (Frontiers in Molecular Biosciences, 2021)
Background & Aims: Activation of the inflammasome NLRP3 (NOD-, LRR- and pyrin domain containing 3) contributes to the development of non-alcoholic fatty liver disease (NAFLD) and progression to non-alcoholic steatohepatitis (NASH). Therefore, this study explored the therapeutic effects of a novel and selective NLRP3 antagonist in a murine dietary model of NASH. Methods: Groups of 12-week-old ApoE-/- mice were fed ad lib for 7 weeks with a methionine/choline deficient (MCD) and western (WD) diet. After 3 weeks of diet-induced injury, mice were injected i.p. with the NLRP3 antagonist IFM-514 (100mg/kg body weight) or vehicle (0.5% carmellose) every day, 5 days/week for a further 4 weeks. Several markers of inflammation, fibrosis and steatosis were evaluated. Whole transcriptome sequencing and panel RNA expression analysis (NanoString) were performed. Results: IFM-514 inhibited IL-1β production in mice challenged with 20mg/kg LPS, and in mouse and human inflammatory cells in vitro. IFM-514 inhibited hepatic inflammation in the in vivo NASH model assessed by H&E staining and in the hepatic gene expression of inflammasome-related proinflammatory cytokines. This effect was associated with significant reduction in caspase-1 activation. Similarly, IFM-514 was efficacious in vivo in MDC-fed ApoE-/- mice, markedly reducing portal pressure, Sirius red staining and 4-hydroxyproline content compared to vehicle-treated mice. Moreover, IFM-514 significantly reduced hepatic steatosis in MCD-fed ApoE-/- mice, as evidenced by NAFLD scores, oil red O staining, hepatic triglycerides and gene expression. In WD treated animals, similar trends in inflammation and fibrosis were observed, although not sufficient IFM-514 levels were reached. Conclusion: Overall, IFM-514 reduced liver inflammation and fibrosis, with mild effects on liver steatosis in experimental murine NASH. Blocking of NLRP3 may be an attractive therapeutic approach for NASH patients.